A comunicação digital nos territórios rurais: um estudo do canal “O Extensionista” no YouTube - Serafin, Renato de Melo (Universidade Federal de São Carlos, 2025)
This original study aims to analyze data from lecture-style videos produced by the "O Extensionista" YouTube channel. The aim was to understand how digital platforms are transforming teaching methodologies and communication in rural areas. In the field of STS, this research demonstrates how technologies and social practices intertwine in rural extension. Dialogical communication in ATER Digital values local knowledge and concrete experiences, while engagement data highlights the importance of formats that respect cultural plurality and rural protagonism, promoting more inclusive and collective extension practices. The guiding question of the study was to understand how videos on the "O Extensionista" YouTube channel, as an ATER Digital initiative, promote engagement and contribute to the innovation and improvement of rural extension practices in Brazil. Furthermore, we sought to answer which attributes of the channel's videos influence public participation and engagement in digital rural extension initiatives. And how do the data on views, likes, and interactions on the channel's videos reflect the effectiveness of Digital ATER initiatives? The research is configured as an exploratory and descriptive investigation. In turn, the collected data were schematized and organized for quantitative analysis. The channel "O Extensionista" has over 96,000 subscribers, has published over 6,800 videos, and has received over 34 million views. The sample for analysis comprises 75 videos generated on the channel from weekly live streams discussing topics related to digital ATER, research, and rural extension worker training. The videos in the sample under investigation have 21,967 views, 1,880 likes, and 1,893 interactions in the chat as their main metrics. The data was organized and categorized by speaker profile, gender, time period, talk/live stream duration, and language. The analyses were constructed using descriptive statistical parameters such as arithmetic mean, standard deviation and coefficient of variation. The most discussed topics were "Scenarios: Challenges and Opportunities in ATER (24%)" and "Technology and Innovation in Rural Extension (22.67%)". The topic with the highest average number of views was "Public Policies, Planning and Regulation of ATER (374)". The most common speaker profile is characterized by rural extensionists and males.

Este estudio es un trabajo original y tiene como objetivo presentar un análisis de datos de videos producidos en formato de conferencia por el canal "O Extensionista" en YouTube. El objetivo fue comprender cómo las plataformas digitales están transformando las metodologías de enseñanza y la comunicación en zonas rurales. En el ámbito de las ciencias, la tecnología y la comunicación (CTS), esta investigación muestra cómo las tecnologías y las prácticas sociales se articulan en la extensión rural, donde la comunicación dialógica en ATER Digital valora el conocimiento local y las experiencias concretas, mientras que los datos de participación resaltan la importancia de formatos que respetan la pluralidad cultural y el protagonismo rural, promoviendo prácticas de extensión más inclusivas y colectivas. La pregunta clave del estudio fue comprender cómo los videos del canal "O Extensionista" en YouTube, como iniciativa de ATER Digital, promueven la participación y contribuyen a la innovación y la mejora de las prácticas de extensión rural en Brasil. Además, buscamos responder qué atributos de los videos del canal influyen en la participación pública y la implicación en las iniciativas de extensión rural digital. ¿Y cómo los datos sobre visualizaciones, "me gusta" e interacciones en los videos del canal reflejan la efectividad de las iniciativas de ATER Digital? La investigación es exploratoria y descriptiva. A su vez, los datos recopilados se esquematizaron y organizaron para su análisis cuantitativo. El canal "O Extensionista" cuenta con más de 96.000 suscriptores, más de 6.800 vídeos publicados y más de 34 millones de visualizaciones. La muestra para el análisis de la investigación comprende 75 vídeos generados en el canal a partir de transmisiones en directo semanales sobre temas de diálogo sobre ATER digital, investigación y formación de extensionistas rurales. Los vídeos de la muestra de investigación tuvieron 21.967 visualizaciones, 1.880 "me gusta" y 1.893 interacciones en el chat como métricas principales. Los datos se organizaron y categorizaron por perfil del ponente, género, periodo, duración de la conferencia/en directo e idioma. Los análisis se realizaron utilizando parámetros estadísticos descriptivos como la media aritmética, la desviación estándar y el coeficiente de variación. Los temas más frecuentemente abordados fueron "Escenarios: Desafíos y Oportunidades en ATER" (24%) y "Tecnología e Innovación en la Extensión Rural" (22,67%). El tema con mayor promedio de visualizaciones fue "Políticas Públicas, Planificación y Regulación de ATER" (374). El perfil de orador más común son los trabajadores de extensión rural masculinos.
Digital communication in rural areas: a study of the "O Extensionista" channel on YouTube
Comunicación digital en el medio rural: un estudio del canal “O Extensionista” en YouTube
Keywords: ATER digital; Comunicação digital; Extensão rural; Métricas YouTube; Digital communication; Rural extension; YouTube metrics; Comunicación digital; Extensión rural; CIENCIAS SOCIAIS APLICADAS